Loss of endogenous RNF43 function enhances proliferation and tumour growth of intestinal and gastric cells. (31st October 2018) - Neumeyer, Victoria; Grandl, Martina; Dietl, Alisa; Brutau-Abia, Anna; Allgäuer, Michael; Kalali, Behnam; Zhang, Yang; Pan, Kai-Feng; Steiger, Katja; Vieth, Michael; Anton, Martina; Mejías-Luque, Raquel; et al.
Abstract: Ring finger protein 43 (RNF43) is an E3 ubiquitin ligase that has been described to be frequently mutated in gastrointestinal cancers. RNF43 downregulation was associated with distant metastasis, TNM stage and poorer survival in patients with gastric and colorectal cancers. Functional analysis has shown that overexpressed RNF43 negatively regulates Wnt signalling by ubiquitinating Frizzled receptors and targeting them for degradation and by sequestering T-cell factor 4 (TCF4) to the nuclear membrane, thereby inhibiting Wnt-mediated transcription. In the stomach, RNF43 overexpression was shown to impair stem-like properties and to be negatively correlated with expression of Wnt-target genes. In this study, we show that RNF43 knockdown enhances the tumourigenic potential of gastric and colorectal cancer cell lines in vitro and in vivo . Thus, loss of RNF43 leads to increased proliferation and anchorage-independent growth as well as increased invasive capacity. In a xenograft model, RNF43 depletion enhanced tumour growth. Furthermore, we established two mouse models in which mutations in the RING domain of RNF43 were introduced. In the intestine and colon, loss of Rnf43 did not induce changes in epithelial architecture or proliferation. In contrast, in the stomach, thickening of the mucosa, hyperplasia and cellular atypia were observed in these mice. Notably, this was independent of elevated Wnt signalling. Together, our results show that RNF43 plays a tumour suppressive role in gastric and colorectal cancer cells and that the loss of its function alters gastric tissue homeostasis in vivo . Abstract : Using in vitro and in vivo models, we provide evidence of an important role for RNF43 in gastrointestinal homeostasis. Thus, loss of RNF43 enhances the tumorigenic potential of intestinal and gastric cancer cells and leads to changes in the gastric epithelial architecture of Rnf43 mutant mice.